Cross Talk between H2O2 and Interacting Signal Molecules under Plant Stress Response - Saxena, Ina; Srikanth, Sandhya; Chen, Zhong (Frontiers in Plant Science, 2016)
It is well established that oxidative stress is an important cause of cellular damage. During stress conditions, plants have evolved regulatory mechanisms to adapt to various environmental stresses. One of the consequences of stress is an increase in the cellular concentration of reactive oxygen species, which is subsequently converted to H2O2. H2O2 is continuously produced as the byproduct of oxidative plant aerobic metabolism. Organelles with a high oxidizing metabolic activity or with an intense rate of electron flow, such as chloroplasts, mitochondria, or peroxisomes are major sources of H2O2 production. H2O2 acts as a versatile molecule because of its dual role in cells. Under normal conditions, H2O2 immerges as an important factor during many biological processes. It has been established that it acts as a secondary messenger in signal transduction networks. In this review, we discuss potential roles of H2O2 and other signaling molecules during various stress responses.